Hotel Sainte Claire's classical Corinthian column. - Gordon, John C. (photographer):::Creator::::::::::::
Photograph shows part of the open patio room which was framed by a Corinthian arcade. The Sainte Claire Hotel opened its doors in 1926 and it is situated at 211 South First Street, San Jose CA.